Implementasi Tanggung Jawab Sosial dan Lingkungan pada PT. Ansaf Inti Resources Sesuai dengan Undang-Undang Nomor 40 Tahun 2007 Tentang Perseroan Terbatas - Revan Rachmad Ramadhan; M. Yasri Fauzil Adhim; Siti Faricha Andi Adkha; Rhemilda Nazwa; Nur Arifudin (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Corporate Social Responsibility is an obligation where companies consider the social and environmental impacts of company activities and are responsible for their contribution to society and the surrounding environment through programs that can improve community welfare. This research aims to analyze how the Corporate Social Responsibility (CSR) program is implemented at PT. Ansaf Inti Resources in accordance with Law no. 40 of 2007 concerning Limited Liability Companies and find out what challenges are faced in implementing the CSR program. The results of this research indicate that the implementation of the CSR program by PT. Ansaf Inti Resources as a company operating in the mining sector has been running well and providing welfare for the community as beneficiaries. However, there are still several challenges in its implementation, including those related to excess budget requests and certainty regarding the status of land that will be used for the construction of public facilities related to CSR.